Basal cell carcinoma developed from an epidermal cyst: A case report and review of the literature - Tomoka Harada; Takeshi Fukumoto; Hideki Shimizu; Chikako Nishigori (PAGEPress Publications, 2021)
Cutaneous epidermal cysts are common benign cysts derived from the epidermis or epithelium of hair follicles, and malignancy originating from epidermal cysts is uncommon. When a cutaneous epidermal cyst turns malignant, it is mostly squamous cell carcinoma, and basal cell carcinoma is rare. We present the case of a 58-year-old man with basal cell carcinoma originating from an epidermal cyst on the buttocks. Histopathological analysis with hematoxylin- eosin (H&E) staining showed the presence of the cyst, the wall of which was partially replaced by a malignant tumor. Moreover, the cyst was filled with malignant tumor cells in some areas. The tumor cells were basaloid, and extended through the dermis down to the subcutaneous tissue in a solid pattern. Immunoperoxidase staining for Ber-EP4 was positive. To our knowledge, there are 11 reported cases of BCC originating from epidermal cysts in English, and we reviewed these reports and examined potential trends. We estimate that some longstanding epidermal cysts may have the potential of malignant transformation, and chronic and repeated irritation might trigger malignancy from epidermal cysts. We emphasize that benignlooking cystic lesions showing progressive growth should be examined histopathologically.